2016
DOI: 10.1057/palcomms.2016.93
|View full text |Cite
|
Sign up to set email alerts
|

What do postdocs need to succeed? A survey of current standing and future directions for Australian researchers

Abstract: When discussing the postdoctoral period in a researcher's life, a lack of career progression often boils down to "is it you, or is it me?" Is it a reduction in the quality of candidates, or the fact that there are now too many candidates for a rapidly shrinking pool of jobs? Australia provides an ideal case study, as a large and decentralized country with a government mandate to build the STEMM (Science, Technology, Engineering, Mathematics and Medicine) workforce. The goal of the present study was 1) to provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 13 publications
2
14
0
Order By: Relevance
“…We found that Family/Carer responsibilities was cited by 9.6% of ECRs as a reason to exit academia. Similar to a previous Australian Postdoctoral Researcher survey 10 , the burden of Family/Carer responsibilities is heavy on both male and female ECRs, suggesting that young parents (male or female) and their families are not sufficiently accommodated by the current system. In interviews, we did identify young mothers on parental leave struggled to continue to run their laboratories, knowing that their staff depend on them, and continued to write publications while on leave out of fear of falling behind.…”
Section: Resultssupporting
confidence: 56%
See 3 more Smart Citations
“…We found that Family/Carer responsibilities was cited by 9.6% of ECRs as a reason to exit academia. Similar to a previous Australian Postdoctoral Researcher survey 10 , the burden of Family/Carer responsibilities is heavy on both male and female ECRs, suggesting that young parents (male or female) and their families are not sufficiently accommodated by the current system. In interviews, we did identify young mothers on parental leave struggled to continue to run their laboratories, knowing that their staff depend on them, and continued to write publications while on leave out of fear of falling behind.…”
Section: Resultssupporting
confidence: 56%
“…Quantitative data was collected from 658 respondents in an on-line survey of ECRs working in a scientific environment in universities and research institutes across Australia. The questionnaire for the survey was developed by first compiling questions, often used in a broader or international context, from research literature including questions from Australian Council of Education Research, The EMCR Forum (part of Australian Academy of Science) 34 , Federation of Australian Scientific and Technological Societies (FASTS), Global Young Academy, National Science Foundation, Nature and Vitae 10,35,36 in order to cover all the themes identified in the literature as matters relating to job satisfaction or dissatisfaction. Some additional questions were created if no suitable question was identified elsewhere.…”
Section: Ethical Approvalmentioning
confidence: 99%
See 2 more Smart Citations
“…By thinking of the good of the wider community, rather than just of personal gain, individuals create value through social enterprise. For evidence of this you need look no further than the postdoctoral training period, a stalwart of many disciplines [13]. Further, the Aristotelian approach which equally weights individuals making ethical decisions and corporations (or professional societies) making ethical decisions demonstrates the need for an individual Honor Code that's supported by the robust framework of a professional code of conduct.…”
Section: Introductionmentioning
confidence: 99%